Foundations of Geometry-IV - Adhikary, Pushpa Raj (Kathmandu University Journal of Science Engineering and Technology, 2009)
DOI: 10.3126/kuset.v5i1.2855 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 151-153